Acclimatization study of Tagetes lucida L. in Egypt and the chemical characterization of its essential oils. Issue 13 (3rd July 2017) - Omer, Elasyed A.; Hendawy, Saber F.; Ismail, Rasha F.; Petretto, Giacomo L.; Rourke, Jonathan P.; Pintore, Giorgio
Abstract: Seeds of Tagetes lucida were imported to Egypt from Canada and propagated under greenhouse conditions in peat moss media. Soil was sandy in texture and the irrigation system was dripping irrigation. The growth parameters were determined at five successive plant ages, fresh and dry weights of herb were determined at three successive plant ages. The yield of aerial parts after 175 days, was about 7.5 Mg/ha. The essential oil (EO) was extracted by hydro-distillation for three hours with a yield of about 0.5% (w/v). The EO of each sample was subjected to gas-chromatography/mass spectrometry analyses to study the chemical composition. The main component of the EO was identified as methyl chavicol which matched over 90% of the whole composition. Chlorophyll a and carotenes increased with increasing plant age in both sites and seasons. Flavonoids decreased with the development of plant age, while the opposite was true with coumarines content. Abstract :